DVT: is it really an SDEC pathway? A retrospective review of SDEC DVT demand and outcomes across Surrey Heartlands ICS - Jalal Kitchlew; Natalie Clayden; Natalie King; Visalakshi Subbian; William Niven; Kelly Baker; Radcliffe Lisk (Clinical Medicine, 2025)
Introduction: This review looks at the current demand and practices of different deep venous thrombosis (DVT pathways across three acute trusts in Surrey Heartlands ICS; Ashford and St Peter's Hospital NHS Foundation Trust (ASPH), Surrey and Sussex NHS Healthcare Trust (SASH) and Royal Surrey County NHS Foundation Hospital (RSCH). The focus is on adherence to National Institute of Health and Care Excellence (NICE) guidance, with the aim of standardising pathways, reducing demand and creating internal capacity within same-day emergency care (SDEC).DVT is a prevalent condition requiring timely intervention to prevent life-threatening complications. Very few patients require admission; thus, DVT management in SDEC consumes valuable resources for minimal bed-day savings.1,2 Materials and Methods: A retrospective review of DVT referrals to SDEC from January 2025 was conducted, reviewing the following:• Source of referral;• Pre-referral Well’s score;• D-Dimer;• Number of scans/rescans and scan outcomes. Results and Discussion: Figure 1 details the results of the study. Figure 2 highlights the usual pathways for DVT referrals into the respective SDEC departments at each Trust. Conclusion: Most scans for suspected DVT are negative because of referral practices not following NICE guidance. Patients interact with multiple clinicians before and after scans across primary and secondary care, incurring significant costs and potentially leading to a poorer experience and clinical risk if the wait for a scan while on anticoagulation exceeds 24 h. Admissions for DVT are rare, with only certain positive cases requiring further review in secondary care. Clinician education on Well’s scoring and the use of point-of-care quantitative D-Dimer tests could reduce scan burdens. However, following the Darzi review to move more services from hospital to the community, a one-stop pathway within a CDC may be better for patients and the healthcare economy by freeing up capacity within SDEC to deliver admission avoidance.3We recommend the following to enhance the pathway in light of our findings: • Clinician education on the value of robust Well’s scoring and clear documentation for referrals for scans; • Quantitative Point of Care Test (POCT) for D-Dimer to reduce inappropriate referrals; • Consideration of DVT as a one-stop CDC pathway condition for community-based workup closer to the patient’s home.